Hepatotoxicity due to antitubercular drugs in multidrug-resistant tuberculosis patients - Oscanoa Espinoza, Teodoro Julio (2022)
Objective: To describe the clinical characteristics of drug-induced liver injury (DILI) in multidrug-resistant tuberculosis (MDR-TB) patients.Materials and methods: A retrospective study conducted in hospitalized patients with MDR-TB and DILI. The criteria of the DILI Expert Working Group were used for the diagnosis of DILI, and the RUCAM (Roussel Uclaf Causality AssessmentMethod) for the causality analysis. The specific association between DILI and antitubercular drugs was established by drug rechallenge or discontinuation and recovery. Results: Seven cases of MDR-TB and DILI are described in this research. The mean age (standard deviation) was 39.10 (3.30) years.Mean DILI occurred 30.40 (27.70) days after starting the treatment. Three (43.00 %) patients presented jaundice. Regarding the type of injury, four (57.00 %) had hepatocellular injury and three (43.00 %) cholestatic injury. Four patients showed mild DILI andthree moderate DILI. All the patients had taken pyrazinamide (pyrazinamide alone: four patients; pyrazinamide and ethionamide: one patient; pyrazinamide, rifampin and isoniazid: one patient; pyrazinamide and rifampicin: one patient). The mean hospital stay was 48.10 (48.70) days. The mean serum alkaline phosphatase (AP), alanine aminotransferase (ALT) and gamma-glutamyltranspeptidase (GGT) were 2.40 (1.10), 7.90 (7.10) and 5.60 (3.70) times the upper limit of normal (ULN), respectively. The meantotal bilirubin was 2.30 (2.00), with a range of 0.50 to 6.40 mg/dl. As part of the discharge plan, quinolones were given to seven patients (levofloxacin: six patients; ofloxacin: one patient) and amoxicillin/clavulanic acid was added to one patient. Conclusions: MDR-TB patients may develop DILI after the first month of treatment. Hepatocellular injury was the mostcommon type of liver injury, and pyrazinamide was the most frequently used antimycobacterial.